Identificación de patologías de base asociadas a pacientes con enfermedad periodontal en las clínicas de adultos de la Antonio Nariño sede armenia-Quindío en el periodo 2020-2021. (2022)
The aim of this project was to evaluate the prevalence and predisposing factors of periodontal diseases associated with base diseases in patients who have attended the UAN clinic, Armenia headquarters, between 2020 and 2021. The population w as made up of medical records of patients between the ages of 29 and 74 years with underlying diseases that could possibly be causing some periodontal pathology, of which those who did not present periodontal disease and who in their medical history did no t present a base pathology were excluded. In the results, the sociodemographic population was characterized with variables such as age, gender, presence of base pathologies and periodontal diseases, taking into account the new classification of said disea se, for this reason only the clinical records of the last years were taken because as from 2020, the completion of medical records with the diagnosis of the new classification of periodontal diseases is required. Taking into account that the data showed th at Arterial Hypertension is the most prevalent underlying disease and along with it there is the existence of a periodontal disease. We concluded that Arterial Hypertension, being a frequent underlying disease in the patients of the UAN clinics, can become a predisposing factor for people with periodontal disease, since it was the most common and was present in the majority of registered patients.